Perlindungan Hukum Terhadap Korban Bullying di Lingkungan Sekolah melalui Edukasi dan Pendampingan - Neng Nazwa Fauziah; Neng Risa Atmarianty; Nanda Amelia Putri; Mia Rahmawati; Frisky Fitri Allya; Clarissa Syahnika Karen; Bunga Fatiha Azzahra; Dellia Deswita Sari; Anjeli Azzahra; Rasya Aulia Eka Hapsari (Sejahtera: Pengabdian Kepada Masyarakat, 2026)
Bullying in the school environment has become a serious issue that affects students’ psychological well-being, social development, and academic performance. The increasing number of bullying cases indicates that awareness regarding legal protection for victims is still relatively low among students, teachers, and parents. This community service activity was conducted at SMK Letris Indonesia 2 Pamulang with the aim of improving understanding of legal protection for bullying victims through educational activities and legal assistance. The method applied in this program used a participatory approach through legal counseling, interactive discussions, and question-and-answer sessions. The implementation was carried out in three stages, namely preparation, implementation, and evaluation. The educational materials focused on forms of bullying, legal consequences, children’s rights protection, and reporting mechanisms for victims. The results of the activity showed an increase in participants’ understanding regarding the importance of preventing bullying and the legal remedies available for victims. In addition, the program encouraged the development of a more responsive attitude among students and teachers toward bullying cases in schools. Therefore, educational and mentoring activities are considered effective in fostering legal awareness and creating a safer school environment.